A comprehensive review of properties of concrete containing lithium refinery residue as partial replacement of cement - Rahman, S.A.; Shaikh, Faiz; Sarker, Prabir (ELSEVIER SCI LTD, 2022)
The escalating demand for lithium battery products in making electronic devices is producing an enormous amount of lithium refinery residue (LRR). This waste is not only an environmental hazard, but most importantly, its proper disposal is very costly. The high cost of Li-battery can be reduced by utilizing this waste in concrete to produce new smart materials in an engineered way to obtain a greater life cycle. The study aims at unravelling a new generation of material that enables its optimization in concrete. Specifically, this paper presents a comprehensive review of physio-chemical properties of some common supplementary cementitious materials (SCMs) and their comparisons with LRR. The previous studies recommended to use 10–20% LRR as a SCM which is suitable for concrete by capturing complex properties like fresh, mechanical, durability and microstructural in line with other pozzolanic materials.